5x-2(x-1)+19)=(x-1)

Simple and best practice solution for 5x-2(x-1)+19)=(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2(x-1)+19)=(x-1) equation:



5x-2(x-1)+19)=(x-1)
We move all terms to the left:
5x-2(x-1)+19)-((x-1))=0
We multiply parentheses
5x-2x+19)-((x-1))+2=0
We add all the numbers together, and all the variables
3x+19)-((x-1))+2=0

See similar equations:

| 5(-2x+7)=6x+3 | | x²-5x=6 | | 5x+3x+12=180, | | 6y-3(y+1)=2(y+3)+3 | | 6x/8-5=4 | | 2+1-7=y | | 3+^x-9=^x+9 | | 5(-2x+7)=6x=3 | | 4(-3)+7y=3 | | v-32=44 | | 2m+7=m+14 | | 14x-7=133 | | 9(x-12)=13(x-12)-3(x+2) | | 34x+2=9 | | 5(p+2)-3(p+3)=0 | | 2(m-1)=6(m+3) | | 2(x+14)-10=14 | | -1/2x+1+3x/2=3 | | 3(4x+2=9 | | 9x+7=187 | | 0=x-1-(3x-5) | | x2−13x=  −5x | | b-29=61 | | 0.65p−7=0.35p | | –t+9=t+5 | | c/5-13=20 | | a-17=-18 | | n-6+3=-4 | | m+m+5+0,5(m+5+m)=36 | | 8t=7t−6 | | 3m+12-2m=4 | | 10-8p=4(4+p) |

Equations solver categories